Effective Photosensitization in Excited‐State Equilibrium: Brilliant Luminescence of TbIII Coordination Polymers Through Ancillary Ligand Modifications. Issue 10 (9th August 2022) - Kitagawa, Yuichi; Moriake, Ryoma; Akama, Tomoko; Saito, Koki; Aikawa, Kota; Shoji, Sunao; Fushimi, Koji; Kobayashi, Masato; Taketsugu, Tetsuya; Hasegawa, Yasuchika
Abstract: Invited for this month′s cover are the collaborating groups of Yuichi Kitagawa, Yasuchika Hasegawa, Tetsuya Taketsugu, and co‐workers at Hokkaido University. The cover picture shows a photosensitizer that has a long excited‐state lifetime and provides strong emissions for Tb III coordination polymers. The photosensitization ability can be considerably altered by changing the ancillary ligands in the Tb III coordination polymers. The results provide new insights on the design of photosensitizers for improving the properties of photo‐functional materials. More information can be found in the Research Article by Y. Kitagawa, Y. Hasegawa, and co‐workers. Abstract : Molecular photosensitizers exhibit efficient light‐absorbing capabilities in photo‐functional materials. This work reports effective photosensitization at excited‐state equilibrium using Tb III coordination polymers. The coordination polymers are composed of Tb III ions (as emission centers), hexafluoroacetylacetonato (as a photosensitizer ligand), and phosphine oxide‐based bridges (as ancillary ligands). The ancillary ligand controls the excited state equilibrium between the photosensitizer and Tb III, allowing the construction of Tb III coordination polymer with high Tb III emission quantum yield (≥70 %). Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.202200151 ).